Repowerment beyond empowerment: collaborative accountability of citizens, corporations and civil servants - Lee, Junesoo (International Journal of Public Sector Management, 2024)
This article conceptualizes and constructs a comprehensive framework that can better help to answer that question – Who is accountable for social and public problems? – theoretically and practically. Tracing the drivers behind two phenomena “accountability hole” and “accountability black hole”, stemming from “pushing power game” and “pulling power game”, respectively, this study considers (1) the three actors of society: citizens (civil society), corporations (market) and civil servants (government), and (2) the principal-agent relationship between the three actors in the face of social and public problems. As a result, the 4CAs framework that contains the three actors’ collaborative accountabilities to one another is presented. The 4CAs model emphasizes (1) all three actors function as agents that are accountable to one another, (2) collaborative accountability beyond collaborative governance and (3) repowering citizens and corporations beyond just empowering them, i.e. returning their inherent rights and obligations to serve one another. The 4CAs model may function as a descriptive and prescriptive lens through which the trilemma between market failure, government failure and citizen failure can be re-assessed and balanced. The model can also be used as a set of indicators for assessing and helping a society to better resolve the social and public problems collectively.